Treatment of painful radiculopathies with capsaicin 8% cutaneous patch - Baron, Ralf; Treede, Rolf-Detlef (Current medical research and opinion, 2017)
Background and objective: The treatment of neuropathic pain due to low-back (lumbosacral) radiculopathies, a common source of neuropathic pain, is challenging and often requires a multimodal therapeutic approach. The capsaicin 8% patch is the first topical analgesic licensed for peripheral neuropathic pain. To evaluate this treatment, a subset of patients with painful radiculopathy (lumbar and cervical, including ventral and dorsal rami) enrolled into the multicenter, non-interventional QUEPP study (Qutenza2 - safety and effectiveness in peripheral neuropathic pain) was analyzed. Methods: Of the 1044 study participants, 50 were diagnosed with painful radiculopathy as only peripheral neuropathic pain syndrome and were eligible for evaluation. Patients received a single treatment (visit 1) with follow-up visits 2-5 at weeks 1-2, 4, 8 and 12. Parameters assessed at all visits included pain intensity, neuropathy symptoms and side effects. Quality of life (SF-12) and painDETECT1 questionnaires were completed at baseline and final visit. Data was analyzed by patch application site and duration of pain. Results: Topical treatment led to a significant decrease of pain intensity between weeks 1/2 and week 12 versus baseline at the application sites representing dermatomes of ventral (N = 26) and dorsal rami (N = 13) of spinal nerves. A significant decline (p ≤ .001) of numeric pain rating scale scores was observed between weeks 1/2 following patch application and the end of observation (week 12) in the overall radiculopathy group (N = 50), and the groups with either 3 months to 2 years (N = 14) or >2 years (N = 23) duration of pain. Pain relief of at least 30% was observed in 50.0%, 71.4% and 39.1% of patients in the respective groups. Four patients experienced in total seven adverse drug reactions (application site pain or pruritus).Conclusion: Effective neuropathic pain relief was observed after patch application within the innervation territories of both dorsal and ventral branches of the spinal nerve. Further controlled randomized trials are indicated.
Gesehen am 29.08.2018